Pengembangan Model Learning Transfer Alumni Peserta Diklat Pengadaan Barang dan Jasa Pemerintah Di Kabupaten Sidoarjo - Dini Asmasuci Malinda (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to see how far the process of learning transfer of training procurement of government goods and services implemented by the Regional Personnel Agency Sidoarjo Regency can be done well. In addition the researchers also see whether the training process has an effect on the implementation in the workplace for trainees who have followed the training. The method used by researchers for this research is to use qualitative research with deductive approach and active participation. After carrying out data collection, data processing and analysis of research results concluded that the input aspects of the learning transfer process has not been maximized because the partici- pants' understanding of the procurement process of goods and services is still theoreti- cal. Viewed from the process aspect of this training is the teaching-learning process that still uses the lecture training model so that the participants only accept the material in theory. While from the output aspect that the granting of alumni of training participants in implementing the materials received during the training but still must be accompanied by an experienced procurement committee. Based on the fact that the learning transfer from the training of procurement of goods and services implemented by the government has not been maximized.